Design and Feasibility Study of A Stand-Alone Home Pv Solar System in Baghdad Climate - Oleiwi, Fadhil Mahmood; Hameed, Jabir Shaker; Dahloos , Jaber.O.Dahloos (Iraqi Journal of Science, 2024)
The question asked by all researchers is when solar panels will replace the national grid, especially in the domestic sector. In this study, a rooftop stand-alone solar electric system is designed to provide all the electrical power to a house in Baghdad-Iraq, using a (How to design PV system) simulation program. The feasibility of this system compared to the performance of the national electric grid and the system of private diesel generators is determined. The proposed solar system capacity is (25 kW), and the space required and the energy payback time are (360 m2 and 7.82 years), respectively. By using the current system, the net CO2 mitigation amount is 499,518.2 tons for 30-year. The kilowatt-hour costs for the subsidized national grid, private diesel generators, and the present solar system is 0.01865$, 0.1509$, and $0.108, respectively. The kilowatt cost can reach 0.25kWh if the battery replacement cost is estimated; so photovoltaic systems are still a good choice to generate electricity instead of using the national grid. If solar PV systems to generate electricity are used instead of the national grid, the financial and environmental profits will be good enough. The reason for the study is because the costs of off-grid solar PV systems are high, no specific studies have emerged on such vital topics. Currently, loans from government banks have reduced the impact of this negative factor